The Effect of Education Program on Knowledge and Role in the Caregiver for Children with Congenital Heart Disease Aged 0 - 3 Years - Wangsawat, Tidarat; Phiban, Anong; Piboonrungroj, Prasert; Hayeese, Wanisa; Chansintop, Sawinee; Dereh, Nurdeenee; A-Kaji, Nirusnee (Princess of Naradhiwas University Journal, 2019)
This quasi - experimental study was designed to determine the effectiveness of a supportive - educative nursing system program on knowledge and caregiver role for caring children with congenital heart disease aged 0 - 3 years at outpatient building of Naradhiwas hospital. Twenty four subjects were purposively selected into the experimental and control group. The experimental group was caregivers who participated in the supportive educational nursing program while the control group was only received routine nursing care. The research instruments were the supportive educational nursing program and handbook for caring children with congenital heart disease. Data were collected by using a two-section questionnaire; caregiver knowledge and caregiver role for caring children with congenital heart disease. The reliabilities for the questionnaires were 0.76 and 0.80 respectively. Data were analyzed by using descriptive statistic and t - test. The research results presented that the experimental group had a different mean scores of caregiver knowledge when compared to before experiment (t = 4.92, p < .001) and were significantly higher than that in the control group (t = 2.81, p < .01). The experimental group had a different mean score of caregiver role in caring when compared to before experiment (t = 4.43, p < .001), but it did not differ when compared to the control group The supportive educational nursing program is an appropriate guideline to educate caregivers so that they have effective knowledge and improve home care of children with congenital heart disease effectively